Photovoltaic Solar Energy Conversion - Bauer, Gottfried Heinrich (Springer, 2016)
This concise primer on photovoltaic solar energy conversion invites readers to reflect on the conversion of solar light into energy at the most fundamental level and encourages newcomers to the field to help find meaningful answers on how photovoltaic solar energy conversion can work (better), eventually contributing to its ongoing advancement.